Development of the conceptual framework for a quality improvement training programme for health professionals in the ministry of health and social services in Namibia - Nangombe, Julia Paul; Amukugo, Hans Justus (International Journal of Health, 2016)
This article describe the process followed by the researcher in the development of the conceptual framework for a quality improvement training programme for health professionals in the Ministry of Health and Social Services in Namibia. The conceptual framework of this study was based on the Practice Orientated Theory of Dickoff (1968) that assisted with explaining the concepts used in developing the quality improvement training programme for health professionals at the health facilities. Dickoff’ s (1968) practice orientated theory consists of the agent, recipients, context, procedure, dynamics, and the terminus. In this study, the agent was a quality specialist, the recipients were health professionals, the context was the health facilities, the dynamics were challenges that health professionals were experiencing; the procedure was the training programme, while the terminus was knowledgeable and skillful health professionals in quality health care delivery.